OC-036 Neuronavigated Repetitive Cerebellar Stimulation Produces Long-Lasting Activation of Human Cortical Swallowing Projections. (4th June 2013) - Vasant, D H; Mistry, S; Jayasekeran, V; Michou, E; Hamdy, S
Abstract : Introduction: Animal studies, human brain imaging and more recently Transcranial Magnetic Stimulation (TMS) suggest a role for the cerebellum in human swallowing. Moreover, paired-pulse cerebellar-cortical TMS delivered in rapid succession (50–200 ms intervals) facilitates pharyngeal motor cortex excitability. We therefore hypothesised that high-frequency (5–20 Hz) repetitive TMS (rTMS) of the cerebellum could modulate pharyngeal motor cortex excitability producing long-lasting changes that may prove to be therapeutically useful for dysphagia after stroke. Methods: In 17 healthy adults (6 female, age range 18–61 yrs), anatomical MR brain scans were acquired. Thereafter participants were intubated with an intraluminal catheter to record pharyngeal electromyography and underwent TMS cortical mapping with neuronavigation to co-localise pharyngeal motor representation bilaterally, hand motor cortex and the cerebellar site which evoked the largest pharyngeal motor response. Subjects were then randomised to receive one of 5 neuronavigated cerebellar rTMS interventions (Sham, 1 Hz, 5 Hz, 10 Hz and 20 Hz, at least 1 week apart) to the cerebellar site evoking the largest baseline pharyngeal responses to single-pulse cerebellar TMS. Bihemispheric pharyngeal cortical excitability (ipsilateral and contralateral cortex to cerebellum site) was measured at baseline and for up to one hour post cerebellar rTMS intervention. Abductor pollicis brevis (APB) recordings were used as control. Interventional data were compared to sham using repeated measures ANOVA. Results: Cerebellar rTMS was tolerated well and delivered at an average intensity of 55% of stimulator output. Compared to Sham, 10Hz cerebellar rTMS increased pharyngeal cortical excitability (F (1.16) = 8.3, * p = 0.01), with maximal size and durational effects seen primarily in the contralateral pharyngeal cortex (+72%, ** p = 0.02, Figure 1 ). By contrast, 1Hz (F (1.16) = 0.3, p = 0.60), 5Hz (F (1.16) = 0.5, p = 0.48), and 20Hz rTMS (F (1.16) = 1.3, p = 0.27) cerebellar conditioning did not significantly alter pharyngeal excitability compared to Sham. APB responses were not significantly different to sham after any intervention. Conclusion: Our data show for the first time that high-frequency (10Hz) cerebellar stimulation can produce long-lasting increases in human pharyngeal motor cortex excitability, with larger and longer-lasting effects of the intervention primarily seen in the contralateral projection. Hence 10 Hz cerebellar rTMS may play a therapeutic role in the treatment of dysphagia after hemispheric stroke. Disclosure of Interest: None Declared